Electricity consumption in UiTM'S hostels, Shah Alam / Haslina Mahmood - Mahmood, Haslina (2004)
One of the important needs in our daily lives is electricity supply. As essential as water, people need this supply to carry out their routine tasks. The supply of electricity service will fulfil the demands on those areas, yet to ensure it is enough to be used. The usage or consumption is not equal in all areas. It depends on the type of appliances used in the building as well as the number of the building occupants who consume this sort of service. Anyhow, people do not mean to use this supply appropriately. As the usage becomes un-equal according to the demand, it is shown that the demand could be increased or decreased, but the consumption of electricity is not necessity to be optimum as the supply. This showed the electricity demand parallels with the supply. As this is the everyday needs for every people, it is mean that electricity need to be controlled and maintained to ensure it is functioning all the time.